Os desafios da inclusão e a prática docente no nível superior: uma questão de direito fundamental - Santos, Marilene Ferreira dos (2014)
This research presents a brief discussion about the process of inclusion in higher learning, seeking to identify in what way the teaching practice takes place with students with Special Educational Needs (NEE), so as to not only guarantee accessibility, but also their permanence in the Higher Learning Institutions (IES). Its general goal is to reflect on the challenges of inclusive education at the higher level and on the pedagogical practice of the professors, identifying the possibilities of insertion of students who need special educational attention. Initially a historical summary is presented of Special Education in Brazil, analyzing various legal documents to outline the perspective on educational legislation. Following this a historical retrospective is made of Higher Learning in Brazil, since the beginnings of school education. The third moment brings an analysis of university teaching practice, from the initial formation up to the continuing education of this professional reflecting on the challenges encountered in teaching in the area of inclusion. In the fourth and last moment alternatives are presented for mediation in inclusive practice through dialog with the theoretical approaches: pedagogical, theological and psychopedagogical. To make effective the theoretical support of the research it was necessary to analyze and reflect the studies of some authors, distributed in the following subthemes: Special Education; Higher Learning; Teaching Practice; Mediation. National and international documents were also analyzed besides the National Guidelines for Special Education (2001), data from the IBGE and CENSO (2010). The methodology used to delineate the research is bibliographic of a qualitative nature which permits a good investigative process.